Guanosine enhances the bactericidal effect of ceftiofur sodium on Streptococcus suis by activating bacterial metabolism - Yue Dong; Xiaona Liu; Shanshan Xiong; Mingyu Cao; Haojie Wu; Long Chen; Mengmeng Zhao; Yadan Zheng; Zhiyun Zhang; Yanyan Liu; Yanhua Li; Qianwei Qu; et al. (Virulence)
The emergence and rapid development of antibiotic resistance poses a serious threat to global public health. Streptococcus suis (S. suis) is an important zoonotic pathogen, and the development of its antibiotic resistance has made the infections difficult to treat. The combination of non-antibiotic compounds with antibiotics is considered a promising strategy against multidrug-resistant bacteria. However, the mechanism by which metabolites act as antibiotic adjuvant remains unclear. Here, we found that guanosine metabolism was repressed in multidrug-resistant S. suis. Exogenous guanosine promoted the antibacterial effects of ceftiofur sodium (CEF) in vitro and in vivo. Furthermore, we demonstrated that exogenous guanosine promoted the biosynthesis of purine pathway, TCA cycle and bacterial respiration, which make bacteria more sensitive to the killing effect of antibacterial. In addition, the function of the cell membrane is affected by guanosine and the accumulation of antimicrobials in the bacteria increased. Bacterial-oxidative stress and DNA damage induced by guanosine is also one of the mechanisms by which the antibacterial effect is enhanced. These results suggest that guanosine is a promising adjuvant for antibacterial drugs and provide new theoretical basis for the clinical treatment of S. suis infection.